Security scheme for mobility management in the internet of things. (2018) - Brian, Oryema; Chun, Seung Man; Jung, Cheol Woo; Park, Jong Tae
A mobility management protocol based on the constrained application protocol (CoAP), called the CoAP-based mobility management protocol (CoMP), was suggested to counteract the constraints of mobile internet protocol version 6 (MIPv6) in the Internet of Things (IoT) environment. CoMP exchanges Binding Update (BU) messages to manage location changes, but BU messages are subject to security vulnerabilities, such as denial of service (DoS), false BU, session hijacking, and man-in-the-middle (MITM) attacks. In this paper, we extend CoMP by proposing a security scheme based on a private key to protect the BU CoMP messages exchanged between the mobile nodes and clients, referred to as private key-based BU for CoMP (PKBU-CoMP). PKBU-CoMP ensures that mobile nodes check and confirm the address ownership and validity of mobile nodes before performing any BU operation. The performance of PKBU-CoMP is analysed both mathematically and using Cooja simulations.